If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -0.5(x + 3) = 0.25(x + -1) Reorder the terms: 8 + -0.5(3 + x) = 0.25(x + -1) 8 + (3 * -0.5 + x * -0.5) = 0.25(x + -1) 8 + (-1.5 + -0.5x) = 0.25(x + -1) Combine like terms: 8 + -1.5 = 6.5 6.5 + -0.5x = 0.25(x + -1) Reorder the terms: 6.5 + -0.5x = 0.25(-1 + x) 6.5 + -0.5x = (-1 * 0.25 + x * 0.25) 6.5 + -0.5x = (-0.25 + 0.25x) Solving 6.5 + -0.5x = -0.25 + 0.25x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.25x' to each side of the equation. 6.5 + -0.5x + -0.25x = -0.25 + 0.25x + -0.25x Combine like terms: -0.5x + -0.25x = -0.75x 6.5 + -0.75x = -0.25 + 0.25x + -0.25x Combine like terms: 0.25x + -0.25x = 0.00 6.5 + -0.75x = -0.25 + 0.00 6.5 + -0.75x = -0.25 Add '-6.5' to each side of the equation. 6.5 + -6.5 + -0.75x = -0.25 + -6.5 Combine like terms: 6.5 + -6.5 = 0.0 0.0 + -0.75x = -0.25 + -6.5 -0.75x = -0.25 + -6.5 Combine like terms: -0.25 + -6.5 = -6.75 -0.75x = -6.75 Divide each side by '-0.75'. x = 9 Simplifying x = 9
| -(4-m)=10 | | 6=-4k+2 | | 20y+2=46 | | 1.33*4=y | | s*7-17=137 | | x^2+x+m-1=0 | | 5(x+3)-3=2(x+8) | | 43-4=y | | 9h-16=74 | | 9m-15=58 | | 5n^2+7n=-2 | | 8x+12y-20= | | 40+16x= | | 3(25-10h+h^2)-20+4h-(75-20)= | | 15x-28= | | 0=x^2-16x-225 | | 6x+27= | | x^7=65 | | 4.9x^2-20x=0 | | 8+(y+2)=4(y-3) | | x+(x*0.25)=500000 | | 3n+4-4=n+20 | | 4t^2-9s^2=0 | | lnx^2-6lnx+5=0 | | (5x-2)-(3x-1)=(4x+3)-(5x-2) | | 7(-1+h)-5(-1)= | | 2lnx+ln(2x-3)=ln(3x-2) | | 0.63=logx | | 3(-5+h)-4(-5)= | | 3(25-2h+h^2)-4+4h-(4-3)= | | 9b^2+42bg+49g^2= | | 3(25-2h+h^2)-4+4h-(3-4)= |